Utilization of Rice Straw for the Production of Hed Nangfa in Non Mak Mun Subdistrict, Sa Kaeo Province - Namee, Janejira; Sooksoi, Panut; Dasri, Chatkasem; Chittabut, Pensri (Area Based Development Research Journal, 2021)
The elimination of rice straw by burning in the community of Non Mak Mun subdistrict, Khok Sung district, Sa Kaeo province resulted in the problem of dust and smoke in the community. This research has applied the zero-waste concept to reduce air pollution and reduce the production cost of mushroom cubes for Hed Nangfa (Pleurotus sajor-caju) by making use of agricultural waste of rice straw. Attended by a total of 34 members, the project process is divided into 2 phases. Phase 1 involves the background study, identification of target areas, comparison of rice straw and rubberwood sawdust as a material for cultivating Hed Nangfa, and analysis of the nutritional value of mushrooms. Phase 2 consists of reviewing and sharing information with the community, brainstorming, analyzing, planning, discussing, disseminating, and exchanging knowledge. The results of the operation showed that the Hed Nangfa yields from rice straw had a lower cost of production than the yield from rubberwood sawdust. Mushroom nutritive value (Percentage of dry matter) indicates that mushroom produced from rice straw has a higher percentage of moisture and fiber, but lower protein than the one produced from rubberwood sawdust. The knowledge dissemination in the community leads to community members’ ability to apply their knowledge for a lucrative sideline, thus earning an extra income of 3,000 baht per month. Since community leaders also disseminate the knowledge of using rice straw for mushroom production to the youth and the elderly, the whole community has been raised awareness of environmental protection and the need to reduce agricultural waste problems in the area.